Visionary Leadership in the Implementation of the Merdeka Curriculum to Foster Student Character and Learning Autonomy in Elementary Schools - Nur Efendi (The Elementary Journal, 2024)
This study examines how visionary leadership supports the implementation of the Merdeka Curriculum to foster student character and learning autonomy in elementary education. The research was conducted at MI Mambaul Hikam Ngubalan Kalidawir using a qualitative case study design involving one principal and six teachers. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using thematic procedures. The findings show that the principal enacted visionary leadership through clear direction, consistent communication, and instructional support that guided teachers in applying student-centered learning. Teachers implemented the curriculum through contextual and flexible activities that integrated character values and promoted independent learning. Students demonstrated increased responsibility, confidence, and active participation, along with improved ability to regulate their learning processes. The alignment between leadership vision and instructional practices created a coherent learning environment that strengthened both character formation and autonomy. The study concludes that visionary leadership is essential in sustaining curriculum reform and enhancing student development in elementary schools.